ANALISIS PERSEPSI, PREFERENSI DAN SIKAP TEUNGKU DAYAH SERTA PENGARUHNYA TERHADAP PERILAKU MENABUNG DI BANK SYARIAH - Riza, Muhammad (IAIN Langsa, 2019)
This study aims to test and analyze the in? uence of perceptions, preferences, and attitude of teungku dayah on saving behavior in Islamic banks. The independent variables used in this study are perceptions, preferences, and attitudes. The dependent variable used in this study is saving behavior in Islamic banks. This study uses quantitative research methods with a survey approach. The population in this study is tengku dayah in the city of langsa totaling 45 tengku dayah, the sample in this study uses probability sampling technique with the type of sampling simple random sampling while the sample size is obtained from the calculation using the Slovin formula with a 5% error rate of 40 tengku dayah. The data sources in this study are primary data in the form of questionnaires. The data source in this study is primary data. Data analysis techniques used were parametric statistics, with multiple linear regression analysis. Measurement of questionnaires answered by respondents used a Likert scale using Statistical Package for the Social Sciences (SPSS) 22. The results of this study indicate that the perception of teungku dayah on saving behavior in Islamic banks has a positive and signi? cant e? ect. While the preference and attitude variables do not a? ect the savings behavior in Islamic banks. While the value of adjusted R2 is 0.62 which shows the in? uence of the independent variable on the dependent variable that can be explained by the equation model is 62% and the remaining 38% is in? uenced by other factors.